Transplantasi Coral sebagai Aksi Peduli Lingkungan untuk Pemanfaatan yang Berkelanjutan - dj, Ashury; ., Juswan; Rachman, Taufiqur; Paroka, Daeng; Baeda, Achmad Yasir; Rahman, Sabaruddin; Umar, Hasdinar; Paotonan, Chairul; Alie, Muh. Zubair; Husain, Firman; Assidiq, Fuad Mahfud; Nasir, Andi Mega Mustika (Faculty of Engineering UNHAS, 2024)
The existence of coral reefs in Indonesia ranks first in area and type. The total area of coral reefs owned by Indonesia is 14% of the total area of coral reefs in the world. Coral reefs have an important value in life, both in terms of ecology to promising economic value. Therefore, the Department of Marine Engineering in collaboration with partners of the South Sulawesi Provincial Tourism Office held an activity “Coral Transplantation as an Environmental Care Action for sustainable use”. This activity has the aim of providing an understanding of the importance of knowledge about the economic and environmental benefits of coral reefs as a beach / sun tourism attraction for domestic and foreign tourists to visit the province of South Sulawesi, especially on Badi Island in Pangkep Regency (Pangkajene Islands). Coral reefs that have been damaged require a long time to recover, due to the slow growth rate of corals. Therefore, human intervention through various methods and means becomes indispensable to improve and rehabilitate the condition of coral reefs. One rehabilitation technique that has been widely recognized and applied in various parts of the world is coral transplantation. By using lecture and discussion methods, as well as coral reef rehabilitation efforts through the real action of coral transplantation. The results obtained showed that there was an increase in knowledge before and after the community participated in the activity and the degradation of coral reefs that occurred could be restored through transplantation of 500 donor corals. The conclusion of this activity indicates that the presentation of material in the form of lectures and discussions has increased community knowledge, and the real action of coral reef transplantation can increase coral reef colonies as a sustainable use.